2008
DOI: 10.2320/matertrans.me200724
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Microstructure and Hardness in Pure Al by Twist Extrusion

Abstract: High purity Al (99.99%) is subjected to severe plastic deformation (SPD) at room temperature using a process of twist extrusion (TE). The microstructure evolution and the related change in microhardness are examined with respect to imposed strain. It is shown that subgrains develop after the first TE pass with a size of $1:6 mm and this size remains essentially the same for further application of TE passes. However, dislocations become less visible within grains and grain boundaries become straight and well-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 11 publications
(24 reference statements)
2
33
0
Order By: Relevance
“…These techniques include equalchannel angular pressing (ECAP) (Ref [5][6][7][8], high-pressure torsion (HPT) ( Ref 3,9,10), torsion-extrusion (TE) (Ref [11][12][13][14], combined tension-torsion (CTT) ( Ref 15,16) and elliptical cross-sectioned spiral equal-channel extrusion (ECSEE) (Ref [17][18][19][20][21]. All of these procedures are capable of introducing large plastic straining and significant microstructural refinement in bulk crystalline solids.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques include equalchannel angular pressing (ECAP) (Ref [5][6][7][8], high-pressure torsion (HPT) ( Ref 3,9,10), torsion-extrusion (TE) (Ref [11][12][13][14], combined tension-torsion (CTT) ( Ref 15,16) and elliptical cross-sectioned spiral equal-channel extrusion (ECSEE) (Ref [17][18][19][20][21]. All of these procedures are capable of introducing large plastic straining and significant microstructural refinement in bulk crystalline solids.…”
Section: Introductionmentioning
confidence: 99%
“…21) In our earlier study, 25) TEM observations and microhardness data of this investigation have been reported. The present report is mostly concentrated on analysis of structure evolution through optical microscopy and Electron Back-…”
Section: Methodsmentioning
confidence: 55%
“…These observations are in a reasonable agreement with earlier results on microhardness and dislocation structure evolution reported in. 25) 4. Summary and Conclusions…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twist extrusion (TE) was introduced [5] as an attempt to scale-up the process of high-pressure torsion. Being promising in the commercial sense, [6] TE enjoyed some interest, which is reflected in continuous research on the subject [7][8][9][10][11][12][13] as well as in the emergence of new SPD methods inspired by the concept of TE. [14][15][16][17][18] In the quest to incorporate TE into the industry, such issues as endurance of the tool are becoming important.…”
Section: Introductionmentioning
confidence: 99%